2019
DOI: 10.1186/s13722-019-0156-2
|View full text |Cite
|
Sign up to set email alerts
|

Does an adapted Dialectical Behaviour Therapy skills training programme result in positive outcomes for participants with a dual diagnosis? A mixed methods study

Abstract: Background Treating severe emotional dysregulation and co-occurring substance misuse is challenging. Dialectical behaviour therapy (DBT) is a comprehensive and evidence-based treatment for borderline personality disorder (BPD). It has been hypothesised that the skills training, which is a facet of the full DBT programme, might be effective for people with severe emotional dysregulation and other co-occurring conditions, but who do not meet the criteria for BPD. However, there is limited research o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
1
8
0
1
Order By: Relevance
“…Flynn and colleagues [62] found a reduction in the number of participants who engaged in binge drinking and use of Class A, Class B and Class C drugs from preintervention to 6-month follow up. Significant reductions in substance use were detected from pre-to post-intervention.…”
Section: The Effect Of Dbt-st On Substance Usementioning
confidence: 99%
See 3 more Smart Citations
“…Flynn and colleagues [62] found a reduction in the number of participants who engaged in binge drinking and use of Class A, Class B and Class C drugs from preintervention to 6-month follow up. Significant reductions in substance use were detected from pre-to post-intervention.…”
Section: The Effect Of Dbt-st On Substance Usementioning
confidence: 99%
“…Flynn and colleagues [62] found that participants with DD reported significant improvements in emotion regulation from pre-intervention to 6-month follow up.…”
Section: The Effect Of Dbt-st On Emotion Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the links between ADHD and ODD suggest that coexisting irritability and dysregulation are mechanisms amenable for change in individual treatment. CBT principles of basic problem-solving and coping skills, as well as dialectical behavior therapy skills (e.g., emotional regulation and distress tolerance) have shown promising results when adapted for treatment of SUD [59, 60].…”
Section: Discussionmentioning
confidence: 99%